Edukasi Perilaku Hidup Bersih dan Sehat Untuk Meningkatkankan Pengetahuan Santri di Pondok Pesantren X Kubu Raya - Nurul Jamil; Nurul Hidayah; Nisma Nisma (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Clean and healthy living behavior problems are most often found at the group level, for example in Islamic boarding schools. Some diseases can occur due to poor PHBS problems, such as skin problems, digestive problems, and even serious illnesses such as hepatitis. The results of observations at the X Kubu Raya Islamic boarding school found that there was insufficient lighting, a less conducive room atmosphere, and even other hygiene problems due to not having good cleand and healthy living behavior discipline. The Purposes of This Study aims to increase knowledge and understanding of cleand and healthy living behavior for students so that there is a behavior change and they can practice it in their daily lives at a boarding school in Kubu Raya Regency. The Methode of This study is quantitative research with an analytic descriptive approach. The number of samples taken was 30 people. Each respondent was given a questionnaire. The results are analyzed up to the frequency data. The average Hygiene knowledge before the education programs, 83% of respondents had low knowledge, 43% of students had low knowledge of washing their hands, and 80% of respondents had low knowledge about the hygiene of their homes. After educating the students' knowledge about personal hygiene, 77% of the respondents had high knowledge, 80% of the students had high knowledge about washing their hands, and 83% of the respondents had high knowledge about the cleanliness of their homes. Based on the results of observations and measurements after education, this PKM activity was able to increase student's knowledge about Clean and Healthy Living behavior